2023
DOI: 10.1039/d3ta01082a
|View full text |Cite
|
Sign up to set email alerts
|

Developing a MXene quantum dot-based separator for Li–S batteries

Abstract: The shuttle effect of polysulfides seriously hinders the practical application of lithium-sulfur (Li-S) batteries, separator modification is supposed to be an effective way to solve this issue. Herein, MXene quantum...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…And we compared recent separator coating efforts and found that our separator thickness occupies a certain advantage. [ 12,48–50 ] We also took scanning electron microscopy photos of the coated surface, as can be seen in Figure S6 (Supporting Information). The morphology of the coated surface shows a porous morphology, which allows the electrolyte to fully infiltrate, and the porosities can accommodate and adsorb more polysulfides, preventing them from passing through the separator and reaching the lithium anode.…”
Section: Resultsmentioning
confidence: 99%
“…And we compared recent separator coating efforts and found that our separator thickness occupies a certain advantage. [ 12,48–50 ] We also took scanning electron microscopy photos of the coated surface, as can be seen in Figure S6 (Supporting Information). The morphology of the coated surface shows a porous morphology, which allows the electrolyte to fully infiltrate, and the porosities can accommodate and adsorb more polysulfides, preventing them from passing through the separator and reaching the lithium anode.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9] Unfortunately, there is still a big gap between the actual and theoretical energy densities of Li-S batteries due to some serious issues, among which the sluggish/incomplete conversion kinetic and shuttle effect of polysuldes results in the attenuation of capacity, severe self-discharge, and loss of active substances. [10][11][12][13] Many studies have been devoted to overcoming this issue. Attributed to the design of functional separators, the electrochemical performance and cycle stability of Li-S batteries have been effectively improved.…”
Section: Introductionmentioning
confidence: 99%
“…6–9 Unfortunately, there is still a big gap between the actual and theoretical energy densities of Li–S batteries due to some serious issues, among which the sluggish/incomplete conversion kinetic and shuttle effect of polysulfides results in the attenuation of capacity, severe self-discharge, and loss of active substances. 10–13…”
Section: Introductionmentioning
confidence: 99%
“…However, some unsolved issues hinder its practical application, such as poor cycling stability and low sulfur utilization caused by the intrinsic insulating nature of sulfur (5 × 10 −30 S cm −1 ), the shuttling of lithium polysulfides (LiPSs) and the large volume expansion (78%). [5][6][7] Plenty of efforts have been devoted to investigating the fundamental mechanism and electrochemical performance optimization approaches of Li-S batteries, and sealing sulfur in the cathode host materials by physical confinement or chemical adsorption is one of the most common methods. [8][9][10] Conductive carbon materials (such as carbon fibers, carbon nanotubes and graphene) with rich porous structures have been widely used as sulfur hosts materials to improve sulfur utilization, suppress the shuttling effect of LiPSs physically and provide sufficient internal space to regulate the volume change.…”
Section: Introductionmentioning
confidence: 99%